Conhecimento estético-artístico no Ensino Médio Integrado da RFEPCT: tensão para a formação humana omnilateral - Souza, Carlos Eduardo de (2023)
Within the great theme “training subjects and aesthetic-artistic production as objectification of the human race”, this study sought to analyze the place occupied by aesthetic-artistic knowledge in Integrated Secondary Education (EMI) within the scope of the Federal Network of Professional Education, Science and Technology (RFEPCT). The thesis resorted to three main sources of data: 1) historiographical literature and records of scientific events; 2) regulations and laws enacted throughout the entire institutionalization of Professional Education in Brazil, especially from its link with Basic Education; and 3) the survey and study of texts (journals/journals, dissertations and theses) published between the years 2008 and 2020, having as object the teaching work at the EMI of the RFEPCT, focusing on aesthetic-artistic contents. The theoretical framework adopted is the Historical-dialectical Materialism, the Historical-Critical Pedagogy, the Historical-cultural Psychology and the critical writings on Vygotsky's art published between 1915 and 1925. In addition to its presence as a curricular component, knowledge aesthetic-artistic can be presented at EMI as experiences, stimulated by different projects (research and extension) carried out by Federal Institutes (IFs). This presence (which occurs in the midst of emptying) is threatened by Law 13.415/2017, which exempts Artistic Education in High School, and also by a set of ultraconservative actions and policies carried out by the “privatizing counter-network” that has taken over the MEC, with great penetration in the federal governments of Temer and Bolsonaro. In a logic of human capital formation or current employability, aesthetic-artistic knowledge proves to be “useless”. Contrary to this ideology and its more harmful effects on the formation of adolescents, considering also the IME as a “crossing” towards an omnilateral formation, we defend that the aesthetic-artistic content represents, in the set of other knowledges considered as “useless” (Philosophy , Physical Education, Sociology), a focus of tension that enhances this path, insofar as, in the face of pressures for merely professional training, it affirms the usefulness of knowledge considered, by the apologists of the national and international bourgeoisie, as “useless ” to workers and their children.